Growth and charge ordering of epitaxial YbFe2O4 films on sapphire using Fe3O4 buffer layer. (14th December 2017) - Fujii, Tatsuo; Numata, Tomoya; Nakahata, Hiroki; Nakanishi, Makoto; Kano, Jun; Ikeda, Naoshi
Abstract: Well-crystallized epitaxial YbFe2 O4 films were prepared on an α-Al2 O3 (001) substrate using an Fe3 O4 buffer layer. Fe3 O4 has a relatively small lattice mismatch with both YbFe2 O4 and α-Al2 O3 . Electron diffraction analysis combined with transmission electron microscopy revealed the epitaxial relationship to be α-Al2 O3 [110](001) ∥ Fe3 O4 [ ](111) ∥ YbFe2 O4 [110](001). Moreover, superlattice spots due the Fe 2+ –Fe 3+ charge order state of YbFe2 O4 were clarified. The Fe 2+ /Fe 3+ ratio in YbFe2 O4 was nearly stoichiometric. The film exhibited a ferrimagnetic transition at ∼220 K and a nonlinear current–voltage characteristic at room temperature. These results confirmed the good crystallinity and stoichiometry of the obtained YbFe2 O4 films.